KEWENANGAN GUBERNUR DKI JAKARTA TENTANG PERUBAHAN NAMA JALAN WILAYAH DKI JAKARTA DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2014 TETANG ADMINISTRASI PEMERINTAH : The authority of the Governor of DKI Jakarta regarding the change of street names in the DKI Jakarta area, as reviewed based on Law Number 30 of 2014 regarding Administration - Vendra, Clarissa Alya Alifia; Wijiningsih, Ninuk (Faculty of Law, Universitas Trisakti, 2024)
The authority of the Governor of DKI Jakarta regarding Determination of Street Names in 2022, is the basis for changing 22 street names in the DKI Jakarta area. This then gave rise to pros and cons in the community, including members of the DPRD DKI Jakarta legislature. The purpose of this study is to describe the preparation and legal consequences of DKI Jakarta Governor's Decree Number 565/2022 concerning changes to street names in the DKI Jakarta area. This study uses a juridical method, is descriptive in nature, and uses secondary data by using qualitative data analysis and drawing conclusions deductively. Based on the results of the analysis, the results obtained are that if it is connected with the Governor of DKI Jakarta Regulation Regarding the Procedure for Preparing Regional Legal Products, then the Decree of the Governor of DKI Jakarta Number 565/2022 is in accordance with the procedure for preparing regional legal products. With the emergence of DKI Jakarta Governor Decree Number 565/2022, it has legal consequences for several parties affected by this decision. When compiling programs or discourses related to changing the names of several roads in the DKI Jakarta area, they are still based on several legal bases that are related not only to looking at one or two legal regulations but also looking at other legal bases in a more objective and widespread manner.